STRATEGI KOMUNIKASI PEMASARAN SURAT KABAR LOKAL DI ERA DIGITAL DALAM INDUSTRI MEDIA CETAK - Djudjur Luciana Radjagukguk (Populis : Jurnal Sosial dan Humaniora, 2017)
The shift in the mass communication world of print media is now moving toward the digital age very rapidly. And causing worry for the print media owners if they do not quickly start  to do something about the media marketing. According to the decreased of newspapers  readers, the owners has to think more harder to develop their media business are able to survive of newspaper in this digital era media industry. In the concept of marketing is clearly explained that company's success in realizing its objectives determined the ability of the company in identifying the needs and wants of market’s target. Efficient and effective, can give the reader satisfaction. In the process of developing marketing communications include several things, namely identifying target audiences, determining communication objectives, designing messages, choosing communication channels compiling communication budgets, determining the IMC (Integrated Marketing Communication) mix, implementing IMC and gathering feedback. The purpose of this research is to know and describe the marketing strategy of local newspaper marketing in digital era. Methods used through observation and in-depth interviews of the company owners and readers. It is expected that the print media, especially local newspapers are not abandoned readers.Keywords: Marketing Communication Strategy, Print Media, Digital Age